Histopathological assessment and staging of large and small vessel disease associated with normal brain aging: Human neuropathology/vascular. (7th December 2020) - Dallaire‐Théroux, Caroline; Saikali, Stephan; Duchesne, Simon
Abstract: Background: Vascular cognitive impairment is the manifestation of diffuse underlying cerebrovascular disease (CVD) that can be assessed at postmortem examination. However, CVD is nonspecific and therefore common in cognitively intact individuals, as prevalence increases with age. There is also an important overlap between CVD and other neurodegenerative conditions, especially Alzheimer's disease, with more than 40% of cases being mixed aetiologies. We aimed to validate a histological scale able to assess the natural progression of small and large vessel lesions associated with normal brain aging, and further understand their potential contribution to cognitive impairment. Method: Brain specimens from 63 cognitively intact participants aged 19 to 84 were examined and rated by two blinded and independent observers using a modified version of the Vascular Cognitive Impairment Neuropathology Guidelines (VCING; Skrobot et al. 2016). The scale focuses on nine anatomical regions and ten histological changes, including vascular wall lesions and secondary tissue damages. Weighted Kappa coefficients were calculated to estimate interrater reliability, and Spearman's rank correlation test was used to calculate regional gradients of vascular load associated with age. Result: Preliminary analyses suggest an inter‐observer agreement ranging from 0.39 to 1.00. Atherosclerosis, arteriolosclerosis, cerebral amyloid angiopathy and perivascular hemosiderin deposits were significantly correlated with age (ρ = 0.76, 0.74, 0.44 and 0.39, respectively; p < 0.005). There was also a trend in the severity of perivascular retraction and myelin loss associated with age (ρ = 0.26 and 0.31, p = 0.04 and 0.01). In arteriolosclerosis, the strongest regional gradients were observed in deeper brain structures (i.e., basal ganglia and thalamus). Conclusion: These results suggest an existing cerebrovascular pathology that accumulates with normal aging, the burden of which can be reproducibly estimated with a modified version of the VCING scale. Our results can be used as normative benchmarks to assess the severity of occurrence. While large vessel pathology is a well‐known risk factor for vascular dementia, the contribution of small vessel disease to cognitive impairment has yet to be established. The use of a dedicated standardized histological staging scale is crucially needed to better understand its clinical implications and identify thresholds of pathological states associated with cognitive decline.